WAY-100635 Alleviates Corneal Lesions Through 5-HT1A Receptor-ROS-Autophagy Axis in Dry Eye - Zhou, Xujiao; Dai, Yiqin; Zhai, Zimeng; Hong, Jiaxu (Frontiers in Medicine, 2021)
Purpose: To explore whether 5-HT1A receptors are involved in the dry eye disease (DED) mouse model and reveal its underlying mechanism. Methods: A C57BL/6J mouse DED model was established via the administration of 0.2% benzalkonium chloride twice a day for 14 days. Corneal fluorescein sodium staining score and Schirmer I test were checked before, and on days 7, 14 and 21 after treatment. The mRNA expression of inflammatory cytokines was measured by reverse transcription-quantitative polymerase chain reaction. Cellular reactive oxygen species (ROS) were detected by 2’,7’-dichlorodihydrofluorescein diacetate assays. Western blot analysis was used to measure the expression levels of autophagic proteins microtubule-associated protein 1 light chain 3 (LC3B-I/II) and autophagy-related gene 5 (ATG5). Results: 5-HT1A receptor agonist (8-OH-DPAT) increased corneal fluorescein sodium staining spots and 5-HT1A receptor antagonist (WAY-100635) decreased them. Treatment with 8-OH-DPAT was associated with the gene expression of more inflammatory cytokines, such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), C-C motif chemokine ligand 2 (CCL2) and C-X-C motif chemokine ligand 10 (CXCL10) compared with treatment with WAY-100635. An increased expression of LC3B-I/II and ATG5 was observed in corneal epithelial cells in the mouse model of DED. 8-OH-DPAT significantly enhanced the expression of LC3B-I/II and ATG5 by disrupting ROS levels. WAY-100635 alleviates autophagy by inhibiting ROS production. Conclusion: Excessive ROS release through 8-OH-DPAT induction can lead to impaired autophagy and increased inflammatory response in DED. WAY-100635 reduces corneal epithelial defects and inflammation in DED, as well as alleviates autophagy by inhibiting ROS production. The activation of the 5-HT1A receptor-ROS-autophagy axis is critically involved in DED development.